If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -1) = x + 3(x + -2) Reorder the terms: 6(-1 + x) = x + 3(x + -2) (-1 * 6 + x * 6) = x + 3(x + -2) (-6 + 6x) = x + 3(x + -2) Reorder the terms: -6 + 6x = x + 3(-2 + x) -6 + 6x = x + (-2 * 3 + x * 3) -6 + 6x = x + (-6 + 3x) Reorder the terms: -6 + 6x = -6 + x + 3x Combine like terms: x + 3x = 4x -6 + 6x = -6 + 4x Add '6' to each side of the equation. -6 + 6 + 6x = -6 + 6 + 4x Combine like terms: -6 + 6 = 0 0 + 6x = -6 + 6 + 4x 6x = -6 + 6 + 4x Combine like terms: -6 + 6 = 0 6x = 0 + 4x 6x = 4x Solving 6x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6x + -4x = 4x + -4x Combine like terms: 6x + -4x = 2x 2x = 4x + -4x Combine like terms: 4x + -4x = 0 2x = 0 Divide each side by '2'. x = 0 Simplifying x = 0
| n/4+7=-13 | | 3+x=3x+13 | | (n/4)+7=-13 | | 12x^3-10x^2-16x=0 | | 14x^2+28x=9 | | 3(6s+5)-12s=3(2s+1)-5 | | 9(x+4)=3(3x+4)+24 | | 0.3(x+90)+0.7x=52 | | 4x-9=-x-9 | | 8x-3=6x+4 | | 8=19-x-2x^2 | | 5*2+4*(8-2)= | | x^3+x^2-8x+12=0 | | 0.20x+.05(16-x)=.10(17) | | 12-x=12 | | 33-.8x=49 | | -2x^2+13x=12 | | 3mn^2+3mn= | | 4x^2+20x+25=27 | | x=7-5y | | 6x+5y=-33 | | (4x+4)+(4x+3)+(4x)=(4x)+(4x)+(5x+4) | | 2xXxX+X=12 | | x²-2x²+2=x | | x/7+x/2=9/14 | | 0.85x+0.05(10-x)=0.10(69) | | (65+20)x=450+20x | | 0.4x-2.2=4.2x+1.8 | | (60+30)x=400+30x | | x^4+3x^2-x-8=0 | | (x-2)*(2x-3)=1 | | 3a+3a+3a= |